Initial manifestation of type I diabetes mellitus as an unusual cause of early post‐operative seizures. Issue 2 (June 2016) - Benova, Barbora; Krsek, Pavel; Sumnik, Zdenek; Kudr, Martin; Komarek, Vladimir; Tichy, Michal
Abstract: We present a case of an 18‐year‐old patient who underwent resective epilepsy surgery for intractable epilepsy caused by focal cortical dysplasia. In the early post‐surgical period, the patient started experiencing atypical seizures refractory to antiepileptic treatment. In due course, abnormally low levels of blood sodium and extremely high levels of blood glucose were discovered. Significant hyperglycaemia was initially ascribed to steroid‐induced diabetes, and antibodies specific to type I diabetes mellitus were subsequently detected, confirming the diagnosis. Following stabilization of glucose and electrolyte levels, the patient became seizure‐free. To our knowledge, this is the first report of presentation of type I diabetes as the cause of early post‐operative seizures. We discuss less common aetiologies of seizures in the early post‐operative period, including metabolic disturbances. Based on our experience, we stress the importance of electrolyte and glucose monitoring in the setting of acute post‐operative seizures.